Horacio D. Cebrero AFSC: A Christian educator par excellence - Cebrero, Horacio D., AFSC (Animo Repository, 1973)
On August 15, 1973, the Institute of the Brothers of the Christian Schools conferred on Horacio D. Cebrero (1908-1982), Elem. '22, HS '27, and AA '29, the highest honor given by the De La Salle Brothers - the Lettres d' Affiliation - for carrying out with zeal and extraordinary dedication the Lasallian mission of giving a human and Christian education to Filipino youth.